If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = 8z + -2 Reorder the terms: -7 = -2 + 8z Solving -7 = -2 + 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. -7 + -8z = -2 + 8z + -8z Combine like terms: 8z + -8z = 0 -7 + -8z = -2 + 0 -7 + -8z = -2 Add '7' to each side of the equation. -7 + 7 + -8z = -2 + 7 Combine like terms: -7 + 7 = 0 0 + -8z = -2 + 7 -8z = -2 + 7 Combine like terms: -2 + 7 = 5 -8z = 5 Divide each side by '-8'. z = -0.625 Simplifying z = -0.625
| 6t^2-60t+126=0 | | -(x-18)+2(x+3)=6(x+4) | | -3n=6(6-n) | | 3x^2+28x=-60 | | 2y=-5(y+1) | | 5k^2=-80 | | -9+5y=-9 | | 5(y-3)=4y | | 8x=4(x+5) | | -(7y+4)-(-6y-5)=-3 | | 4(n-2)=-8 | | 5Z+5=-3 | | 1.6r+7=1.2r+15 | | 9(2x-2)=3(6x+4) | | -7y+22=3y-8 | | 4+9p-2=8p+23-6p | | x(x+1)=x+x+1+29 | | 28x^9y^9-7w^7x^6y^7= | | 13-5t=4t-23 | | -5x+5=65 | | 8n-18=6n+6 | | 44x^2+29x-3=0 | | 4x^3-7x^2-24x+42= | | 2x^2-x=-3 | | 8x+6x+4x=0 | | 9p-9=-3p+6 | | 8r+7r=90 | | 7p+6=5p-4 | | 6y^5-27y^4+27y^3= | | 3k^2-2k-8= | | 2=-5w-5 | | k^2+8= |